ANTESEDEN DARI EMPLOYEES’ ENGAGEMENT: SEBUAH MODEL MODERATED MEDIATION DARI PERCEIVED ALTERNATIVE JOB OPPORTUNITIES, EMPLOYEES’ ATTITUDE DAN EMPLOYEES’ MOTIVATION DOSEN DI UNIVERSITAS “X” [THE ANTECEDENTS OF EMPLOYEES’ ENGAGEMENT: A MODERATED MEDIATION MODEL OF LECTURER’S PERCEIVED ALTERNATIVE JOB OPPORTUNITIES, EMPLOYEES’ ATTITUDE AND EMPLOYEES’ MOTIVATION AT “X” UNIVERSITY ] - Indrawan, Indrawan (Polyglot, 2023)
Abstract This study aims to investigate the role and potential of mediating and moderating variables which are the antecedents for Employees' Engagement (EE) at University “X” by developing and testing an empirically integrated model to study the mediating role of Employees' Attitude (EA) and Employees' Motivation (EM) on the relationship between Transformational Leadership (TL) and EE being moderated by Perceived Alternative Job Opportunities (PAJO). This study uses a quantitative research approach with survey research methods (non-experimental). The data collection method was carried out through an E-questionnaire for 98 lecturers at the "X" university. Data is analyzed using PLS-SEM resulting in PAJO does not moderate the mediation of EA and EM between TL and EE. Bahasa Indonesia Abstrak Penelitian ini bertujuan untuk mempelajari peran dan potensi variabel mediasi dan moderasi yang merupakan anteseden bagi Employees’ Engagement (EE) di universitas “X” dengan mengembangkan dan menguji sebuah model yang terintegrasi secara empiris untuk mempelajari peran mediasi Employees’ Attitude (EA) dan Employees’ Motivation (EM) terhadap hubungan Transformasional Leadership (TL) dan EE yang dimoderasi oleh Perceived Alternative Job Opportunities (PAJO). Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan metode penelitian survey (non-eksperimental). Metode pengumpulan data dilakukan melalui E-kuesioner terhadap 98 dosen di universitas “X”. Analisis Data menggunakan PLS SEM dimana hasil penelitiannya adalah PAJO tidak memoderasi hubungan TL dan EE yang dimediasi oleh EA dan EM.